The availability of alternative devices for the management of the difficult airway in public emergency centres in the Western Cape - Jooste, Willem Johannes Lodewyk (Stellenbosch : Stellenbosch University, 2017)
The published article is available in this repository at http://hdl.handle.net/10019.1/125681